2016
DOI: 10.1111/jphp.12606
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic review on medicinal plants used for rheumatoid arthritis in traditional Persian medicine

Abstract: Objectives Rheumatoid arthritis (RA) is a chronic, inflammatory, autoimmune disease, which affects synovial tissue in multiple joints. Although conventional treatments of RA commonly alleviate the symptoms, high incidence of adverse reactions leads to research tendency towards complementary and alternative medicine. As various medicinal plants are traditionally used for the management of symptomatologies associated with RA in Persian medicine, we reviewed medicinal literature to confirm their efficacy in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 69 publications
(168 reference statements)
0
16
0
1
Order By: Relevance
“…Numerous previous studies have reported that inflammatory factors have an important role in the development of RA. Despite this, the etiology of this disease remains uncertain (6,12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous previous studies have reported that inflammatory factors have an important role in the development of RA. Despite this, the etiology of this disease remains uncertain (6,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous previous studies have reported that inflammatory factors have an important role in the development of RA. Despite this, the etiology of this disease remains uncertain (6,12,13).Tripterygium is an ingredient in traditional Chinese medicine with anti-inflammatory effects that is sourced from Anhui, Zhejiang, Hunan, Guangxi, Guizhou, Yunnan and Sichuan provinces. (5R)-5-hydroxytriptolide (LLDT-8) is the extract of Tripterygium leaves, the main ingredients of which have a number of anti-inflammatory and immunoregulatory functions (14).…”
mentioning
confidence: 99%
“…The famous traditional Persian medicine scientists, including Rhazes (854-925 CE), Avicenna (980-1037 CE), Jorjani (1042-1137 CE), Tonkaboni (17th century CE), and Aghili Khorasani (17th-18th century CE) had a pivotal contribution to the growth of medical and pharmaceutical practices. 18 – 20 …”
mentioning
confidence: 99%
“…Pro-inflammatory cytokines such as interleukin (IL)-1, IL-8, and tumor necrosis factor-α can stimulate COX-2 that leads to overproduction of PGE2. [ 32 ] It has been shown that acacetin protects dopaminergic cells against MPP + -induced neuroinflammation in vitro and in vivo . [ 33 ] It is also reported that FAs have anti-inflammatory properties and, therefore, might be useful in the management of inflammatory and autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%